2011
DOI: 10.1089/pho.2010.2928
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Laser Irradiation on Peripheral Mammalian Nerves and Relevance to Analgesic Effects: A Systematic Review

Abstract: This review has identified a range of laser-induced inhibitory effects in diverse peripheral nerve models, which may reduce acute pain by direct inhibition of peripheral nociceptors. In chronic pain, spinal cord changes induced by LI may result in long-term depression of pain. Incomplete reporting of parameters limited aggregation of data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0
16

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(144 citation statements)
references
References 82 publications
3
125
0
16
Order By: Relevance
“…In in vivo studies, it has been shown that laser irradiation can partially or totally inhibit nerve conduction and can affect conduction velocity and action potential amplitude [31]. Studies on rat models showed that laser radiation inhibits Aδ and C fibre transmission of nociceptive stimuli induced by cold/heat, chemicals and proinflammatory substances [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In in vivo studies, it has been shown that laser irradiation can partially or totally inhibit nerve conduction and can affect conduction velocity and action potential amplitude [31]. Studies on rat models showed that laser radiation inhibits Aδ and C fibre transmission of nociceptive stimuli induced by cold/heat, chemicals and proinflammatory substances [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de não haver uma padronização dos parâmetros do laser para obtenção de efeito analgésico, existem algumas sugestões para tratamento da dor musculoesquelética com energias que variam de 6 a 24 J por ponto para o laser infravermelho (820 a 830 nm), sendo recomendado 6 J para lesões agudas pequenas e acima de 10 J para aquelas maiores 8 , as quais também são recomendadas pela Associação Mundial de Laserterapia (WALT). No presente estudo foram empregadas energias de 3, 6 e 12 J, as quais são localizadas dentro da janela terapêutica 49 , com o objetivo de avaliar qual delas seria melhor para obtenção de hipoalgesia.…”
Section: Discussionunclassified
“…Some literature reported positive results for tissue repair and anti-inflammatory effects when the range of 5-55 mW/cm2 was employed [103][104][105], while higher irradiances of 300-1730 mW/cm2 was recommended for analgesic purposes [106].…”
Section: Irradiancementioning
confidence: 99%